CHARACTER BUILDING IMPLANTED IN ENGLISH LESSONS AS PRESCRIBED IN 2013 CURRICULUM - Ira Audina Pratiwi; Soni Mirizon; Rita Inderawati (English Review: Journal of English Education, 2021)
This study aimed at finding out the English teachers’ understanding of character building prescribed in 2013 Curriculum, the integration of character building in English teaching and learning, the reasons teachers apply certain character(s), and the challenges of the integration of character building in English teaching and learning. This is a qualitative study in a case study design. The participants were two English teachers of secondary school in Palembang. The data were collected through questionnaire, interview, observation, and documentation. The data of this study were analyzed qualitatively. The data obtained from the observations and interviews were analyzed through thematic analysis by identifying, classifying, arranging, and clarifying them. Data from documentation were read thoroughly and matched with criteria set. Data from questionnaire were classified based on the frequency of characters taught during classroom teaching. The results revealed that in understanding the character, the teachers were in the level of good and fair. It was found that there were 15 out of 18 characters taught, mostly in implicit manner; only 6 characters were explicitly mentioned in each lesson plan. The reason of applying the characters was due to the characters recommended matched with teaching materials taught. Teachers encountered challenges in determining the recommended character to teach and in managing students’ different characteristics